Model repair of Time Petri Nets with temporal anomalies. Issue 7 (2015) - Basile, F.; Chiacchio, P.; Coppola, J.
Abstract: In this paper the model repair of Time Petri net models with temporal anomalies is considered assuming that the nominal model is known and an observed timed sequence is given. The nominal model is updated online, if the durations of system activities change while their initial instant does not, without modifying the structure of the PN nominal model but just extending the firing interval of transitions. The approach requires the solution of a Mixed-Integer Linear Programming.